Dynamical Analysis of Modified Mathematical Model of Social Media Addiction - Juhari, Juhari; Fikrina, Zulfa Akfi; Alisah, Evawati; Sujarwo, Imam (CAUCHY: Jurnal Matematika Murni dan Aplikasi, 2024)
In this study, there is no division between addiction in the mild and severe stages. Therefore, it is necessary to divide the stages of addiction because the healing is clearly different. Therefore, in this study, a modified dynamic analysis of the Social Media addiction model is carried out to obtain a valid model that can be implemented in real life. This study aims to find the stability of changes in the Addicted variable which is divided into two, namely Social Media addiction in the mild stage and Social Media addiction in the severe stage  There are six models that have been modified in this study, namely, individuals who do not have Social Media but are vulnerable to addiction , individuals who have Social Media but are not yet at the addiction stage , individuals infected with Social Media addiction in the mild stage , individuals infected with Social Media addiction in the severe stage , individuals who are recovering from Social Media addiction , individuals who are completely recovered from Social Media addiction . The steps of dynamic analysis include determining the equilibrium point, analyzing the stability of the equilibrium point, finding the basic reproduction number, numerical simulation of all variables. The results showed that the population of individuals infected with Social Media addiction in the mild stage  was at a value of 1.6112 with t = 4 years while the population of individuals infected with Social Media addiction in the severe stage  was at a value of 36.542 with t = 4 years. This study provides information that the dynamic analysis carried out on the modified mathematical model of Social Media addiction shows a stable condition.